Analysis of Factors Enhancing Green Purchase Intention Among Consumers of Environmentally Friendly Products in Indonesia - Satria, Muhamad Teguh Wafa; Haryanto, Totok; Rachmawati, Erny; Endratno, Hermin (IJOSMAS, 2026)
This study aims to analyze the factors influencing green purchase intention among consumers of environmentally friendly fashion products in Indonesia, focusing on environmental attitude, green brand image, green perceived value, and green trust. The research employs a quantitative approach through an online questionnaire distributed using purposive sampling, resulting in 118 respondents who met the specified criteria. Data were analyzed using PLS-SEM to evaluate the relationships among variables in the research model. The findings indicate that environmental attitude, green brand image, and green trust have a significant positive effect on green purchase intention, while green perceived value does not have a significant effect on green purchase intention. These results highlight the importance of sustainability values and the credibility of environmental claims in driving purchasing decisions. The study is limited by the scope of product categories and sample characteristics. Future research is recommended to expand the research objects, such as involving multiple brands or fashion products, consider mediating variables, or apply a cross-industry comparative approach.